PENGARUH PERSEPSI WAJIB PAJAK TENTANG KUALITAS PELAYANAN FISKUS TERHADAP KEPATUHAN WAJIB PAJAK DENGAN PREFERENSI RISIKO SEBAGAI VARIABEL MODERASI - Wardani, Dewi Kusuma; Sukarte, Ketut (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2023)
The purpose of this study was to determine the effect of taxpayer perceptions of tax authorities' service quality on taxpayer compliance with risk preference as a moderating variable. This study uses a quantitative design. The data was obtained from distributing online questionnaires with the Google form. The sampling technique used is incidental sampling. The number of samples used amounted to 217 respondents. In this study several tests were carried out such as validity test, reliability test, classic assumption test, f-test, determinant coefficient test, t-test with a significance value of 0.05. The results of the study prove that the taxpayer's perception of the quality of tax authorities' services has a positive effect on taxpayer compliance. Risk preference cannot moderate the influence of taxpayer perceptions about the quality of tax authorities' services on taxpayer compliance